Acetylated 1, 3‐diaminopropane antagonizes abscisic acid‐mediated stomatal closing in Arabidopsis. (2nd July 2014) - Jammes, Fabien; Leonhardt, Nathalie; Tran, Daniel; Bousserouel, Hadjira; Véry, Anne‐Aliénor; Renou, Jean‐Pierre; Vavasseur, Alain; Kwak, June M.; Sentenac, Hervé; Bouteau, François; Leung, Jeffrey
Summary Faced with declining soil‐water potential, plants synthesize abscisic acid (ABA), which then triggers stomatal closure to conserve tissue moisture. Closed stomates, however, also create several physiological dilemmas. Among these, the large CO2 influx required for net photosynthesis will be disrupted. Depleting CO2 in the plant will in turn bias stomatal opening by suppressing ABA sensitivity, which then aggravates transpiration further. We have investigated the molecular basis of how C3 plants resolve this H2O–CO2 conflicting priority created by stomatal closure. Here, we have identified in Arabidopsis thaliana an early drought‐induced spermidine spermine‐N1‐acetyltransferase homolog, which can slow ABA‐mediated stomatal closure. Evidence from genetic, biochemical and physiological analyses has revealed that this protein does so by acetylating the metabolite 1, 3‐diaminopropane (DAP), thereby turning on the latter's intrinsic activity. Acetylated DAP triggers plasma membrane electrical and ion transport properties in an opposite way to those by ABA. Thus in adapting to low soil‐water availability, acetyl‐DAP could refrain stomates from complete closure to sustain CO2 diffusion to photosynthetic tissues.